Optimal Multiperiod Contracts and the Gain from Enduring Relationships under Private Information - Townsend, Robert M. (Journal of Political Economy, 1982)
[Informational asymmetries can play a key role in explaining the existence and nature of multiperiod contracts. In an illustrative risk-sharing model even relatively short (two-period) contracts can be mutually beneficial if there is private information, though one-period contracts suffice otherwise. Further, contracts which are Pareto optimal relative to the environment and the information structure are defined and partially characterized. An example illustrates how otherwise inefficient intertemporal tie-ins can be used optimally to mitigate incentive problems. The obvious borrowing-lending schemes are not private-information Pareto optimal; in these, period-by-period actions are not sufficiently constrained. Discounting affects the form of the optimal contract but none of these qualitative conclusions.]